Predictors of late arrhythmic events after generator replacement in Brugada syndrome treated with prophylactic ICD - Migliore, Federico; Martini, Nicolò; Calo', Leonardo; Martino, Annamaria; Winnicki, Giulia; Vio, Riccardo; Condello, Chiara; Rizzo, Alessandro; Zorzi, Alessandro; Pannone, Luigi; Miraglia, Vincenzo; Sieira, Juan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: predictors of late life-threatening arrhythmic events in BrS patients who received a prophylactic ICD implantation remain to be evaluated. The aim of the present long-term multicenter study was to assess the incidence and clinical-electrocardiographic predictors of late life-threatening arrhythmic events in Brugada syndrome (BrS) patients with a prophylactic implantable cardioverter defibrillator (ICD) and undergoing generator replacement (GR).Methods: the study population included 105 patients (75% males;mean age 45±14years) who received a prophylactic ICD and had no arrhythmic event up to first GR. Results: the median period from first ICD implantation to last follow-up was 155 (128-181) months and from first ICD Implantation to the GR was 84 (61-102) months. During a median follow-up of 57 (38-102) months after GR,10 patients (9%) received successful appropriate ICD intervention (1.6%/year). ICD interventions included shock on ventricular fibrillation (n=8 patients), shock on ventricular tachycardia (n=1 patient) and antitachycardia pacing on ventricular tachycardia (n=1 patient). At survival analysis, history of atrial fibrillation (log-rank test;P=0.02), conduction disturbances (log-rank test;P<0.01), S wave in lead I (log-rank test;P=0.01) and first-degree atrioventricular block (log-rank test;P=0.04) were significantly associated with the occurrence of late appropriate ICD intervention. At Cox-regression multivariate analysis, S-wave in lead I was the only independent predictor of late appropriate ICD intervention (HR9.17;95%CI 1.15-73.07;P=0.03). Conclusions: the present study indicates that BrS patient receiving a prophylactic ICD may experience late appropriate intervention after GR in a clinically relevant proportion of cases. S-wave in lead I at the time of first clinical evaluation was the only independent predictor of persistent risk of life-threatening arrhythmic events. These findings support the need for GR at the end of service regardless of previous appropriate intervention, mostly in BrS patients with conduction abnormalities.